Manajemen Laba, Leverage, Pertumbuhan Penjualan, Penghindaran Pajak: Peran Moderasi Komisaris Independen - Emanuel, Richard; Trisnawati, Estralita; Firmansyah, Amrie (E-Jurnal Akuntansi, 2023)
The research aims to empirically examine the effect of earnings management, leverage, and sales growth on tax evasion. In addition, this study also examines the moderating role of independent commissioners in the relationship between the independent variables and the dependent variable. This study uses data in the form of financial statements of the consumer goods sector listed on the IDX for the 2018-2021 period. The total sample used in this study was 180 sample data selected by purposive sampling method. Hypothesis testing was carried out using multiple linear regression analysis with panel data. The test results show that earnings management and leverage have no effect on tax evasion, while sales growth has a negative effect on tax evasion. The results of the study concluded that the independent commissioner has no moderating role in the effect of earnings management on tax evasion and the effect of leverage on tax evasion. However, independent commissioners can strengthen the negative effect of sales growth on tax evasion. Keywords: Debt Policy; Earnings Quality; Tax Planning; Sales Growth; Corporate Governance